A rare case of a 2:2:1 ternary cocrystal of pyridine sulfides and trithiocyanuric acid. Issue 8 (20th July 2021) - Wzgarda-Raj, Kinga; Książkiewicz, Olga; Palusiak, Marcin
Abstract : A rare case of a 2:2:1 ternary cocrystal consisting of trithiocyanuric acid and two pyridine sulfides is reported, of which 1, 4‐bis(pyridin‐4‐yl)tetrasulfane is characterized by X‐ray diffraction for the first time. Abstract : We report a rare case of a 2:2:1 ternary cocrystal consisting of two trithiocyanuric acid molecules, two bis(pyridin‐4‐yl) sulfide molecules and 1, 4‐bis(pyridin‐4‐yl)tetrasulfane, namely, 1, 3, 5‐triazinane‐2, 4, 6‐trithione–4‐(pyridin‐4‐ylsulfanyl)pyridine–1, 4‐bis(pyridin‐4‐yl)tetrasulfane (2/2/1), 2C3 H3 N3 S3 ·2C10 H8 N2 S·C10 H8 N2 S4 . This interesting crystal structure with five neutral molecules per asymmetric unit was synthesized and characterized by means of X‐ray diffraction (XRD) experiments and quantum‐chemical modelling. Among various specific interactions, hydrogen and halogen bridges have a significant role in stabilizing the crystal structure. In particular, the role played by stacking interactions has been revealed by structure analysis and theoretical calculations. Crystallization was spontaneous and reproducible. One of the components, 1, 4‐bis(pyridin‐4‐yl)tetrasulfane, has been characterized by XRD for the first time.